Beverages from coffee beans of Arabica as a source of health-promoting and psychoactive compounds - Sosna, Patrycja Róża (Journal of Education, Health and Sport, 2019)
Introduction: Coffee is one of the most widely consumed beverage in the world. Its popularity stems from organoleptic, psychoactive properties and health-promoting compounds content. Thanks to caffeine, it has stimulant properties, warming effects, and also positively affects the digestive system. In turn, frequently occurring polyphenols are potentially protective agents against chronic neurodegenerative diseases, cancer and diabetes. They have been associated with antioxidant effects and support the cardiovascular system.Objective: The aim of the study was to compare the coffee beverages obtained from ground beans of Arabica species from different countries in terms of content of compounds with health- and psychoactive properties. In the study medium roasted coffee beans from Brazil, India, Costa Rica and Guatemala were used. All the samples were ground to obtain three degrees of fragmentation (fine, medium, coarse). Steaming ground beans were conducted using the same conditions. In the obtained beverages the content of caffeine and polyphenols were examined, and their effect on the antioxidant potential of the beverages.Results: It was found that beverages prepared from coffees of different origins differed in terms of caffeine and polyphenols content. The least of the compounds was in beverages with Guatemala coffee, while beverages with India and Brazil coffee contained more of them. The fineness of beans also affects the composition of the beverages. Generally, greater fragmentation increased the extraction of caffeine and polyphenols. The antioxidant potential of the beverages depended more on the country of origin of the coffee than fineness of beans. The beverages from Guatemala and Costa Rica coffee were characterised by greater antioxidant potential.